2006
DOI: 10.1103/physrevd.73.107901
|View full text |Cite
|
Sign up to set email alerts
|

1/q2corrections and gauge/string duality

Abstract: We make an estimate of the quadratic correction based on gauge/string duality. Like in QCD, it proves to be negative and proportional to the string tension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(108 citation statements)
references
References 25 publications
4
103
1
Order By: Relevance
“…The resulting wave equations are equivalent to the radial equation of a two-dimensional oscillator, previously found in the context of mode propagation on AdS 5 × S 5 , in the light-cone formulation of Type II supergravity [79]. Also, equivalent results follow from the introduction of a gaussian warp factor in the AdS metric for the particular case of massless vector modes propagating in the distorted metric [80]. A different approach to the soft-wall (SW) consists in the non-conformal extension of the algebraic expressions found in the previous section to obtain directly the corresponding holographic LF wave equations.…”
Section: Soft-wall Holographic Modelmentioning
confidence: 73%
“…The resulting wave equations are equivalent to the radial equation of a two-dimensional oscillator, previously found in the context of mode propagation on AdS 5 × S 5 , in the light-cone formulation of Type II supergravity [79]. Also, equivalent results follow from the introduction of a gaussian warp factor in the AdS metric for the particular case of massless vector modes propagating in the distorted metric [80]. A different approach to the soft-wall (SW) consists in the non-conformal extension of the algebraic expressions found in the previous section to obtain directly the corresponding holographic LF wave equations.…”
Section: Soft-wall Holographic Modelmentioning
confidence: 73%
“…Various solutions of modified AdS background are discussed, namely, corresponding gauge theory are modified N = 4 SYM's. On the other hand, there are several works [14,15,16] to generalize the AdS/CFT correspondence to more realistic QCD. While there are several works to search elaborate string/supergravity solutions in full 10 dimensional space-time, whose holographic dual has properties similar to QCD, there are also many trials to directly construct five dimensional holographic dual of QCD by demanding to reproduce desired properties of QCD, which are referred to the AdS/QCD in our paper.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, we adopt the model by Karch et al [15] which possesses a confinement mechanism with the help of a non-trivial dilaton background. It is worth mentioning an alternative model proposed by Andreev and Zakharov [16]. They adopt a deformed AdS 5 metric but a trivial dilaton field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this model it can be shown that the partonic log of the two point vectorial Green function receives 1 /Q 2 -corrections differently from what holds in perturbative QCD Operator Product Expansion (OPE) [19][20][21][22]. Nevertheless, we find extremely interesting to have a model where the Regge region would be analytically related to the deep Euclidean region even though with the wrong OPE.…”
Section: Introductionmentioning
confidence: 96%